2008
DOI: 10.1539/joh.o7005
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cardiac Strain among Drillers of Two Different Age Groups in Underground Manual Coal Mines in India

Abstract: A Comparison of Cardiac Strain among D r i l l e r s o f Tw o D i f f e r e n t A g e G r o u p s i n Underground Manual Coal Mines in India:Ratnadeep SAHA, et al. Department of Physiology, Universal College of Medical Sciences, NepalCardiac strain was evaluated in terms of working heart rate (WHR), relative cardiac cost (RCC), net cardiac cost (NCC) and other recovery indices among six younger (mean age 34.2 ± 2.7 yr) and sixteen older (mean age 48.9 ± 5.4 yr) drillers working in a manual underground coal min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Many of the issues affecting work in hot environments, which were first addressed in South African mining operations in the 1920s, remain unresolved. (1)(2)(3)(4) Although limits for work and heat stress in hot mines have also been partially examined in Germany, (5,6) Turkey, (7) India, (8) Australia, (9) and the United States, (10) the need to combat personnel heat exposure in Canadian mines is comparatively new but becoming an increasingly important issue. In recent years, the economic incentive to mine deeper has created new and unique challenges for the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the issues affecting work in hot environments, which were first addressed in South African mining operations in the 1920s, remain unresolved. (1)(2)(3)(4) Although limits for work and heat stress in hot mines have also been partially examined in Germany, (5,6) Turkey, (7) India, (8) Australia, (9) and the United States, (10) the need to combat personnel heat exposure in Canadian mines is comparatively new but becoming an increasingly important issue. In recent years, the economic incentive to mine deeper has created new and unique challenges for the industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, little empirical data are available on the physiological impact of current workload on nurses during daily shifts. Identifying whether workloads exceed the physiological limits is imperative to the determination of workload allocation and shift scheduling (Saha et al, 2008). Furthermore, there are increasing concerns regarding the negative effects of twelve hour shifts upon nurses' wellbeing and work performance (Trinkoff et al, 2006;Keller, 2009;Geiger-Brown and Trinkoff, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The environmental heat load might be one of the reasons for increased cardiovascular stress. There are several strong evidences regarding consistence of higher cardiovascular stress among underground hot workplace coal miners of German [34] and India [15].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been found upon the workers of china clay mine. Very few studies are sporadic on coal miners [15][16][17] and other occupations [18].…”
mentioning
confidence: 99%